Intervenção ao autismo via ensino de cuidadores - BORBA, Marilu Michelly Cruz de (Universidade Federal do Pará, 2020)
Autism Spectrum Disorder is a developmental disorder highly prevalent in the world population. Behavior-Analytic Intervention to autism is being pointed internationally as one of the most effective ways of intervention, provided that it is individualized, intensive, early, and extensive. Under such conditions, although highly effective, Behavior-Analytic Intervention is inaccessible to most of the affected population in Brazil. Having said that, intervention via caretakers may result as an efficient and viable alternative. Nevertheless, research on the efficacy of such ways of indirect intervention are rare, particularly in Brazil. The purpose of the present work was to develop an intervention program via caretakers and evaluate its efficacy to teach basic skills (“sit down”, “wait”, “greeting”, “attend when called by name”, “visual tracking”, “imitation with and without objects”). Six children diagnosed with ASD (with ages up to six years old) participated together with their respective caretakers. The caretakers were given conceptual and practical teaching and were supervised one a week. The teaching programs were carried out mainly by discrete trial. The results show efficacy of the intervention via caretakers, with the teaching programs being well succeeded to develop the above mentioned basic repertoires. Also, this research documented maintenance and generality of the taught repertoire. Additionally, the present dissertation includes other two components that are reports of basic research on the acquisition of tacts and mands, carried out in the context of the caretaker-based intervention program reported in the first component. The viability of such subsequent studies shows that a well-designed environment to deliver behavior-analytic services is also adequate to the development of basic research on procedural variables implied in the acquisition of specific repertoires.